THE EFFECT OF INFLATION, LABOR FORCE PARTICIPATION RATE AND EXPORTS ON ECONOMIC GROWTH IN INDONESIA - Rizka Nadilla; Ichsan Ichsan (Journal of Malikussaleh Public Economics, 2023)
This study examines the effect of inflation, labor force participation rate and exports on economic growth in Indonesia. This study analyzes the data using the Autoregressive Distributed Lag (ARDL) model with time-series data from 1990 to 2021 obtained from the World Bank and the Central Statistics Agency of Indonesia. The results conclude that in the short and long terminflation has a negative and significanteffect on economic growth in Indonesia. In the short term, labor force participation rate hasa positive and significant effect on economic growth in Indonesia. In the long term, labor force participationrate has a positive but insignificant effect on economic growth in Indonesia. In the shortand longterm, exports have a positive and significant effect on economic growth in Indonesia. Based on the research results, it is suggested that inflation control, improvement in the quality of the labor force, and export enhancement are necessary.